THE 80TH BIRTHDAY ANNIVERSARY OF PROFESSOR OLEKSANDR LUKIENKO - Mykhailov, V.; Ivanik, O.; Yanchenko, V.; Kravchenko, D. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The consideration is given to scientific and pedagogical activity of the prominent Ukrainian geologist, Doctor of geological and mineralogical sciences, professor Oleksandr Ivanovich Lukienko. His work activity as a scientist, teacher and administrator has been described. His contribution to development of Ukrainian and world geology was outlined.